Rapidly Progressive Bilateral Infective Endocarditis Involving Prosthetic Material After Repaired Tetralogy of Fallot: A Case Report - Hiroki Ikeuchi; Masao Hirano; Masashi Kabasawa (Clinical Case Reports, 2026)
ABSTRACT Infective endocarditis after repaired tetralogy of Fallot can rapidly progress when prosthetic material is involved. We report bilateral multivalvular endocarditis undetected by transthoracic echocardiography but identified by transesophageal echocardiography. Early diagnosis and timely surgical intervention are essential to prevent extensive intracardiac spread.